Maternal Characteristics and Socio-Economic Factors as Determinants of Low Birth Weight in Indonesia: Analysis of 2017 Indonesian Demographic and Health Survey (IDHS) - Wulandari, Fatqiatul (MDPI, 2022)
Although low birth weight (LBW) is still a major health problem in Indonesia, studies about determinants of LBW with large sample sizes are still limited. This study aimed to examine the association between LBW and maternal characteristics, as well as socio-economic backgrounds in Indonesia. A secondary analysis of 2017 Indonesian Demographic and Health Survey (IDHS) was conducted, specifically using the questionnaires for women of childbearing age. A bivariate chi-square analysis and a multivariate logistic regression analysis were performed. As many as 6.7% of infants were born with LBW. In terms of maternal characteristics, women who gave birth to twins were 20.30 times more likely to have infants with LBW (p < 0.001). Women with birth intervals of <24 and ≥24 months were likely to have LBW infants (p < 0.05). Complications during pregnancy were also associated with LBW (1.99 times higher than women with no complications) (p < 0.001). In terms of socio-economic factors, women with higher education and higher wealth index were less likely to give birth to infants with LBW. Additionally, marital status and type of residence were also significantly associated with a higher risk of LBW. In conclusion, LBW was associated with maternal characteristics and socio-economic backgrounds among women of childbearing age in Indonesia, including twin births, birth interval, and pregnancy complications as well as educational attainment, wealth index, marital status, and type of residence.